AGRO-CHEMICAL INPUTS USE IN INDONESIA DURING 1970-1989: IS ITS CONTRIBUTION ON RICE PRODUCTION SIGNIFICANT? - Joko Mariyono (Pusat Studi Lingkungan Hidup Universitas Gadjah Mada, 2006)
Agro-chemical inputs (fertilizar and pesticides), have contributed in growing economics of Indonesia, which in 1970-1989 demonstrated a spectacular increase in rice production. Since the agro-chemical inputs prossess two contradictive characteristics of enhancing yield and preventing yield loss on one hand, and threatening human health and environment on the other hand, a study that reviews the real contribution of agro-chemical inputs on rice production in needed. The objective of the study is to determine whther or not the contribution of agro-chemical inputs on rice production in the 1970-`1989 periods is significant. Estimation is conducted by using time series data comprising four main factors of rice production: rice-planted area, nitrogen-fertilizer, chemical pesticides, and tectonogical progress. Data were compiled from GOI report. The results of estimation indicate that the increase in rice production during 1970-1989 was not caused by increasing chemical pesticide use, but by the enlargement of planted rice are, rise in nitrogenous fertilizer use, and technological progress.